Kelayakan Modul Pembelajaran IPA Berbasis STEM untuk Meningkatkan Karakter Rasa Ingin Tahu - Siti Sofia Nurlatifah; Retno Triwoelandari; Suyud Arif (Universitas Indraprasta PGRI Jakarta, 2023)
The aim of this research is to find out whether the STEM-based IPA learning module to increase the character of this curiosity is worthy of use or not. This research uses the ASSURE research model in Research and Development methods. (Research and Development). The validation sheet of the learning module was used as a research tool that evaluated by three experts namely: material experts, linguists, and design experts. The results of this research achieved a success rate of 92% in terms of materials with highly qualified category, 95% in terms Of Languages With Very Qualified Category and 77.94% In terms Of Designs With Qualifiable Category. After the experts have completed the validation test, the student evaluated the learning modules at the individual, small group, and large group test levels. As a sample this research was carried out in the 5th SDIT Khoiru Ummah, Leuwisadeng Bogor district. Based on the ratings of respondents to the individual trial obtained a score of 92.30% with the category highly eligible. Small group test scores are 86.60% with highly qualified category and large group tests are 88.60% in highly qualified categories. It can be concluded that based on the validation by experts (materials, languages, and designs) and respondents, the development of a STEM-based IPA learning module to enhance the character of students' curiosity is worthy to be used to facilitate educators and learners' participation in learning.